ANALISIS PERAN YKAN DAN DUKUNGAN KEBIJAKAN PEMERINTAH DESA TERHADAP KEBERLANJUTAN KONSERVASI MANGROVE BERBASIS KOMUNITAS DI TELUK SULAIMAN - Valalien Zata Amani; Khoirul Amin; Mohamad Dziqie Aulia Al Farauqi (LPPM Universitas Abdurrab, 2026)
This study aims to analyze the role of the Nusantara Nature Conservation Foundation (YKAN) and the support of village government policies in achieving the sustainability of community-based mangrove conservation in Teluk Sulaiman, Berau Regency, East Kalimantan. The research adopts a qualitative approach with a case study method to examine the dynamics of interaction between YKAN, the Forum for Environmental Conservation (Forlika), and the village government, as well as how community ecological experiences influence conservation participation. The findings reveal the existence of epistemological disparities between the scientific approach promoted by YKAN and local ecological knowledge, limitations in the implementation of village policies in terms of authority and budget allocation, and a maritime identity crisis that affects the level of community engagement. These findings affirm that mangrove conservation is a socio-political process that reshapes the relationship between coastal communities and their living space. Theoretically, this study contributes to the development of Green Theory by highlighting the intermestic dimension of mangrove conservation, in which local practices contribute to the global agenda of climate change mitigation. Practically, the study recommends strengthening institutional capacity, optimizing the use of FCPF-CF funds, and institutionalizing multi-stakeholder coordination to enhance conservation sustainability.